2000
DOI: 10.1203/00006450-200008000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for the Common LCHAD Mutation (1528G>C) Is Not a Major Cause of HELLP Syndrome and the Prevalence of the Mutation in the Dutch Population Is Low

Abstract: Long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) deficiency is an autosomal recessive disorder of mitochondrial fatty acid oxidation. Apart from life-threatening metabolic derangement with hypoketotic hypoglycemia, patients often show liver disease, cardiomyopathy, and neuropathy. A common mutation (1528GϾC) in the gene coding for the ␣-subunit of the mitochondrial trifunctional protein harboring LCHAD activity is found in 87% of the alleles of patients. LCHAD is considered a rare disorder with only 63 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 23 publications
0
19
1
Order By: Relevance
“…Mutation analysis in patients in China, Japan and Korea reveals zero patients carrying this mutation [17,34,3641]. In contrast, European countries report allele frequencies from as low as 1:680 in the Netherlands to a high of 1:79 in one region of Poland [30,32]. The carrier rate in the United States has never been investigated to our knowledge.…”
Section: Hadha or Hadhb Mutations And Retinopathymentioning
confidence: 99%
“…Mutation analysis in patients in China, Japan and Korea reveals zero patients carrying this mutation [17,34,3641]. In contrast, European countries report allele frequencies from as low as 1:680 in the Netherlands to a high of 1:79 in one region of Poland [30,32]. The carrier rate in the United States has never been investigated to our knowledge.…”
Section: Hadha or Hadhb Mutations And Retinopathymentioning
confidence: 99%
“…The presence of these abnormalities so soon after birth strongly suggests prenatal accumulation of these fatty acid metabolites. As in LCHAD deficiency, it may be expected that in our patient with CACT deficiency, long‐chain acylcarnitines have accumulated also 15 . Shekhawat et al 8 showed a cytotoxic effect of these metabolites as they inhibit mitochondrial FAO, impair ATP production and are known to damage sarcolemmal membranes 16 .…”
Section: Discussionmentioning
confidence: 88%
“…5 ). Accumulation of acylcarnitines has been linked to fatty acid oxidation deficiency due to a defect in carnitine-acylcarnitine translocase [55] , and acylcarnitines directly reflect the oxidation rate of fatty acid [56] , [57] . Previously, a clinical report of a mother who has had previous miscarriages but gave birth to a baby with a lethal deficiency of CACT indicated that maternal heterozygosity for CACT deficiency with fetal homozygosity for the same deficiency may contribute to impaired metabolism and toxic metabolites formation in both fetus and placenta [58] .…”
Section: Discussionmentioning
confidence: 99%